In vivo skin dose measurement in breast conformal radiotherapy - Soleymanifard, Shokouhozaman; Aledavood, Seyed Amir; Noghreiyan, Atefeh Vejdani; Ghorbani, Mahdi; Jamali, Farideh; Davenport, David (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: Accurate skin dose assessment is necessary during breast radiotherapy to assure that the skin dose is below the tolerance level and is sufficient to prevent tumour recurrence. The aim of the current study is to measure the skin dose and to evaluate the geometrical/anatomical parameters that affect it. Material and methods : Forty patients were simulated by TIGRT treatment planning system and treated with two tangential fields of 6 MV photon beam. Wedge filters were used to homogenise dose distribution for 11 patients. Skin dose was measured by thermoluminescent dosimeters (TLD-100) and the effects of beam incident angle, thickness of irradiated region, and beam entry separation on the skin dose were analysed. Results : Average skin dose in treatment course of 50 Gy to the clinical target volume (CTV) was 36.65 Gy. The corresponding dose values for patients who were treated with and without wedge filter were 35.65 and 37.20 Gy, respectively. It was determined that the beam angle affected the average skin dose while the thickness of the irradiated region and the beam entry separation did not affect dose. Since the skin dose measured in this study was lower than the amount required to prevent tumour recurrence, application of bolus material in part of the treatment course is suggested for post-mastectomy advanced breast radiotherapy. It is more important when wedge filters are applied to homogenize dose distribution.